UTILIZATION OF SAGO DREGS AS RUMINANT FEED BY USING THE FERMENTATION METHOD: LITERATURE REVIEW - Titi Lahanda Susanti; Ratu Safitri; Abun Hasbuna Padmadijaya (Balai Bioteknologi, Badan Pengkajian dan Penerapan Teknologi (BPPT), 2022)
ABSTRACT Every year there is a change in the stock of ruminant feed that occurs in the rainy season and water shortages in the dry season. Utilization of agricultural waste as an alternative feed is one way to overcome these problems. One of the wastes that have the potential to be used as feed ingredients is sago waste. Sago pulp is a waste that is rich in lignocellulose, namely cellulose. Several biotechnology applications in ruminant feed fermentation can improve properties such as taste, aroma, shelf life, texture and nutritional value of food. Fermentation using mold or yeast, as well as bacteria or a mixture of various microorganisms can increase the nutrients in the feed needed by ruminant feed. Processing of lignocellulosic materials is required to obtain optimal degradation results. The degradation process will convert lignocellulosic material into raw materials that are easily digested by the ruminant. Enzymes produced by microorganisms can increase crude protein, crude fat, carbohydrates, crude fiber, vitamins and minerals. Thus, the fermentation method of sago dregs and its use as feed can increase the nutritional value, so that productivity can be increased when given as feed. ABSTRAK Setiap tahun terjadi perubahan stok pakan ternak ruminansia yaitu pada musim hujan dan kekurangan air pada musim kemarau. Pemanfaatan limbah pertanian sebagai pakan alternatif merupakan salah satu cara untuk mengatasi permasalahan tersebut. Salah satu limbah yang berpotensi untuk dimanfaatkan sebagai bahan pakan adalah limbah sagu. Ampas sagu merupakan limbah yang kaya akan lignoselulosa yaitu selulosa. Beberapa aplikasi bioteknologi dalam fermentasi pakan ternak ruminansia dapat meningkatkan sifat-sifat seperti rasa, aroma, umur simpan, tekstur dan nilai gizi makanan. Fermentasi menggunakan kapang atau khamir, serta bakteri atau campuran berbagai mikroorganisme dapat meningkatkan nutrisi dalam pakan yang dibutuhkan pakan ruminansia. Pengolahan bahan lignoselulosa diperlukan untuk mendapatkan hasil degradasi yang optimal. Proses degradasi akan mengubah bahan lignoselulosa menjadi bahan baku yang mudah dicerna oleh ruminansia. Enzim yang dihasilkan oleh mikroorganisme dapat meningkatkan protein kasar, lemak kasar, karbohidrat, serat kasar, vitamin dan mineral. Dengan demikian, metode fermentasi ampas sagu dan pemanfaatannya sebagai pakan dapat meningkatkan nilai gizi, sehingga produktivitas dapat meningkat bila diberikan sebagai pakan.